Improving the Methodology for Ensuring Population Safety During Emergencies - Ziyodillaevich, Mamatov Nurbek (EDUMALSYS Journal of Research in Education Management, 2025)
This study analyzes the influence of the human factor, building architecture, technical means, and several other variables on the evacuation process, as well as the methodology for organizing population evacuation during emergencies. Particular attention is given to how these factors affect the efficiency and safety of movement along escape routes for different categories of the population, including vulnerable groups, within various types of buildings, structures, and residential areas. The evacuation methodology was refined and improved through computer-based simulations, which enabled the systematic evaluation and optimization of evacuation scenarios under conditions of heightened stress and risk.